STUDENTS’ PERCEPTION OF ENGLISH ONE FOR TWENTY (EOT) PROGRAM TOWARDS THEIR SELF CONFIDENCE IN SPEAKING SKILL - Wahyu Prastyawan (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
English is one of the languages used throughout the world as an international language. Thus, it is not surprising that speaking is an important component that must be mastered by students in expressing an idea or information directly. However, the process of learning to speak English has several problems, one of which is a lack of confidence. Confidence is one of the non-linguistic aspects that can affect students' speaking ability. The existence of the English One for Twenty (EOT) program helps students in speaking English, especially in increasing self-confidence.The researcher used a qualitative design with the variable perception of EOT participants on the students' self-confidence in speaking ability. Then, the participants of this research are students who are members of the EOT program which consists of 30 students from various majors at the University of Islam Malang. In collecting data, researchers used questionnaires and online interviews. The questionnaire was adopted from (Anjelyn Susanti Purba 2014) and Selfy Aveline Talilah (2013) for interviews.Based on the results of the study showed that having self-confidence in speaking skills is very important. It is proven that students who are members of the EOT program positively perceive the importance of having self-confidence in speaking skills. Based on the result, further researchers can expand this research by using other skills such as; reading, listening, and writing. On the other hand, you can use more instruments to get more information from respondents. Thus, it is hoped that future researchers can find more complete and perfect results.